Serous borderline ovarian tumors in long-term culture: phenotypic and genotypic distinction from invasive ovarian carcinomas. Issue 6 (1st October 2008) - Woo, M. M.M.; Salamanca, C. M.; Miller, M.; Symowicz, J.; Leung, P. C.K.; Oliveira, C.; Ehlen, T. G.; Gilks, C. B.; Huntsman, D.; Auersperg, N.
Abstract : Serous borderline ovarian tumors (SBOTs) are differentiated, slow growing, noninvasive, and have a better prognosis than their invasive counterparts, but recurrence and progression to invasive carcinomas are common, and unlike high-grade serous carcinomas, they tend to be nonresponsive to chemotherapy. However, due to a lack of culture systems and animal models, information about the properties of SBOT and their changes with neoplastic progression is extremely limited. Our objective was to establish a cell culture model for SBOTs and to characterize their phenotype and genotype. We compared cultures derived from two SBOTs, one of which was a short-term culture containing a BRAF mutation but few other cytogenetic changes while the other culture developed into a spontaneously immortalized permanent cell line and had numerical and structural chromosomal abnormalities but lacked RAS/BRAF mutations. Both cultures formed whorl-like epithelial colonies and resembled low-grade invasive carcinomas by their secretion of CA125 and oviduct-specific glycoprotein, production of matrix metalloproteinases, E-cadherin expression, and telomerase activity. Other characteristics associated with neoplastic transformation, including invasiveness, anchorage-independent growth, and tumorigenicity, were not observed. Importantly, cell motility was reduced in both lines, likely contributing to the lack of invasiveness. The results reveal a striking phenotypic similarity between the two cell lines, regardless of their cytogenetic diversity, which suggests that their characteristic phenotype is regulated to a large degree by epigenetic and environmental factors. In conclusion, we have established the first permanent SBOT cell line, which provides a new model to elucidate the undefined relationship of SBOTs to invasive ovarian carcinomas.